Application of current knowledge and trends in sports training of top level volleyball teams in the Czech Republic - Lehnert, M.; Stierand, J.; Chmelik, F.; Hanik, Z. (Telesna Kultura, 2010)
To achieve the best results in top volleyball it is necessary to analyze the current state and to react adequately to development trends, which characterize modern volleyball. OBJECTIVES: The goal of the study was to acquire information regarding how do top volleyball coaches of senior and junior volleyball teams in the Czech Republic put current knowledge and trends in volleyball sport training and coaching in practice. METHODS: We created a survey consisting of 31 questions, which were divided into 5 areas: respecting of the current requirements of game performance in training, training efficiency, conditioning, coaching and psycho-social aspects. The survey was sent to 49 coaches, 24 of them replied (response rate 49%). RESULTS: The research shows that coaches do not apply all important knowledge and trends for players` preparation (76% of correct answers in total). Groups of coaches were further divided to subgroups according to gender of the trained teams, age categories, coaches work load and 1st and 2nd class coaches. The comparison of the answers in the subgroup of coaches with respect to segregated areas has only pointed at a difference between male and female teams in the area of psycho-social training aspects (Z = 1.756; p = 0.079; d = 0.717). The comparison of coaches` groups answers to individual questions show that: a) coaches of male teams base their training sessions on real game situations and choose the content of the exercises with the ball more thoroughly (Z = 1.85; p = 0.07; d = 0.75) and require defensive game combinations at the net more often (Z = 1.81; p = 0.07; d = 0.74); b) junior teams are behind (Z = 1.90; p = 0.06; d = 0.77) senior teams in the number of training hours with the ball a week and in making conditions for successful realization of offensive game combinations with fast set (Z = 2.10; p = 0.04; d = 0.86); c) 1st class coaches within the scope of condition training pay more attention to core training (Z = 2.16; p = 0.03; d = 0.94), more than 2nd class coaches; d) full-time coaches seem to be more professional (Z = 1.73; p = 0.08; d = 0.74) than part-time coaches, however, within the scope of fitness training with the ball based on real game situations, full-time coaches are surprisingly less rigorous (Z = 1.96; p = 0.05; d = 0.80). CONCLUSIONS: The study pointed to possible deficiencies in training and coaching of top volleyball teams in the Czech Republic. There were also some significant differences between monitored groups of coaches. It is necessary to be aware that the results of this research are limited by the low number of respondents.